Modulation of the spread of pathological tau in vitro and in vivo. (20th December 2022) - Panzi, Chiara; Restani, Laura; Novelli, Elena; Guarascio, Rosellina; Cheetham, Michael; Wray, Selina; Caleo, Matteo; Schiavo, Giampietro
Abstract: Background: In tauopathies such as Alzheimer's disease, tau aggregates are known to propagate across functionally connected neuronal networks, but the mechanisms underlying this process are poorly understood. Several lines of evidence support the hypothesis that tau release is dependent on neuronal activity. Pathological tau can be found in the extracellular space, inside synaptic vesicles, and other synaptic compartments, or in a free form. We aim to test both in vitro and in vivo the effect of selected botulinum neurotoxins (BoNTs) and tetanus neurotoxin (TeNT) on the release of tau from synaptic terminals. BoNTs and TeNT enter synapses and cleave different synaptic SNARE proteins, impairing synaptic vesicle fusion and release and they may affect tau spread. Method: Primary neurons were cultured in MFCs and transduced with lentiviruses expressing human tau (hTau) isoforms. Cells were treated with BoNTs and stimulating agents. The content of hTau in the culture media was quantified with an enzyme‐linked immunosorbent assay (ELISA). Adeno‐associated viral vectors (AAVs) expressing hTau were injected in the vitreous, and the superior colliculus (SC) and lateral geniculate nucleus (LGN) areas were analysed through immunohistochemistry. Result: The release of the 1N4R mutant hTau (P301S), but not the wild‐type form, is affected by botulinum neurotoxin type A (BoNT/A) and neuronal stimulation, which, respectively, significantly decreases and increases the release of P301S hTau. The AAV constructs are correctly expressed in both primary neurons and in retinal ganglion cells (RGCs), and brain sections of SC and LGN were analysed. Conclusion: Clostridial neurotoxins represent a powerful tool for the study of neurons and synapses. Using BoNT/A, we showed that hTau release is modulated by specific SNARE complex components and differs depending on the isoform. The use of other BoNT types in both in vitro and in vivo models will help us to identify the SNARE proteins involved in tau release. This approach will provide novel insights on the mechanisms controlling tau release from synaptic terminals and identify novel molecular targets for the development of therapeutic interventions to treat tauopathies.